2007
DOI: 10.1007/s11414-007-9057-3
|View full text |Cite
|
Sign up to set email alerts
|

Pretrial Court Diversion of People with Mental Illness

Abstract: Court diversion is a method of administering justice compassionately for persons with mental illness (PMI). Evidence-based practices of this intervention were identified by reviewing the existing literature. Findings suggest that: (a) formal case finding procedures are important for the early identification of mentally ill offenders in need of services, (b) stable housing enhances the possibility that the divertee will remain in regular contact with her or his treatment provider, and (c) active case management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…Though there is debate about whether treatment of SMHC contributes to reduced recidivism (e.g., 3537 ), there is little debate about the appropriateness of ensuring that offenders with SMHC receive good MH treatment as part of pre- or post-plea court diversion, 38,39 or as part of justice system community supervision. 40 Further, malleable risk factors for offending among those with SMHC are similar to those in the general population including school failure, 4145 alcohol and substance use, 4147 unemployment, 46 poverty, 36 and homelessness.…”
Section: Introductionmentioning
confidence: 99%
“…Though there is debate about whether treatment of SMHC contributes to reduced recidivism (e.g., 3537 ), there is little debate about the appropriateness of ensuring that offenders with SMHC receive good MH treatment as part of pre- or post-plea court diversion, 38,39 or as part of justice system community supervision. 40 Further, malleable risk factors for offending among those with SMHC are similar to those in the general population including school failure, 4145 alcohol and substance use, 4147 unemployment, 46 poverty, 36 and homelessness.…”
Section: Introductionmentioning
confidence: 99%
“…Diversion initiatives target offenders charged with theft, prostitution, driving while impaired (DWI), 1 domestic assault, and those who have substance abuse or mental health problems associated with criminal behavior (Clark & Henry, 2003;Fields, 1994;Hartford, Carey, & Mendonca, 2007;Harvey, Shakeshaft, Hetherington, Sannibale, & Mattick, 2007;James, 2006;Shafer, Arthur, & Franczak, 2004;Steadman, Morris, & Dennis, 1995;Sullivan et al, 2007;Swaminath, Mendonca, Vidal, & Chapman, 2002;Thompson, Reuland, & Souweine, 2003;Toborg, Yezer, & Carver, 1991). This is due primarily to the high level of support among county or district court attorneys that diversion garners for these types of offenses (Potter & Kakar, 2002).…”
Section: Uses Of Pretrial Diversionmentioning
confidence: 99%
“…Many have suggested that the deinstitutionalization movement has lead to the increased trend to process the mentally ill through the criminal justice system instead of being hospitalized (A bramson, 1972;Baillargeon et al, 2010;Green, 1997;Hartford, Carey & Mendonca, 2007;Perez et al, 2003;Slate & Johnson, 2008). This phenomenon is often referred to as the "criminalization of mentally disordered behavior" (Abramson, 1972;Baillargeon et ai., 2010;Green, 1997;Hartford et ai., 2007;Perez et ai., 2003;Slate & Johnson, 2008).…”
Section: Deinstitutionalization To Criminalizationmentioning
confidence: 99%
“…The use of evidence based practice is likely most influential in how the criminal justice system responds to certain populations of offenders, such as those who are homeless, mentally ill, or addicted to substances (Golder et aI., 2005;Hartford, et …”
Section: Effective Services For the Homelessmentioning
confidence: 99%
See 1 more Smart Citation